KEBOCORAN TEPI RESTORASI SEMEN IONOMER KACA DENGAN BAHAN FUJI® II, FUJI®VII (WHITE) DAN FUJI® VII (PINK) - Lestari, Sri; Aju F, Dwi Warna; K, Annisa; F., Hidayatul (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Glass Ionomer Cement (GIC) is restoration material commonly used in dental practice.One of GIC strengths is its low level of microleakage. GIC is applied on the cavity with low mastication weight like Fuji® II, Fuji® VII (white), Fuji® VII ( pink). The aim of this study was to observe the microleakage level of cervical restoratin edge with Fuji® II, Fuji® VII ( white), and Fuji® VII ( pink).Each group contained of 6 samples of GIC filling of cervical third buccal surface , immersed in methylene blue solution, cut across linguo-buccal and subsequently observed on its edge microleakage using binoculer microscope indicated with the depth of methylene blue penetration.The result showed that edge microleakage from the lowest up to the highest were Fuji® VII pink, Fuji® VII white and Fuji® II. Anova statistical analysis showed no significant differences among the three groups.